2018
DOI: 10.1038/s41416-018-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

The sVEGFR1-i13 splice variant regulates a β1 integrin/VEGFR autocrine loop involved in the progression and the response to anti-angiogenic therapies of squamous cell lung carcinoma

Abstract: Overall, these results reveal an unexpected pro-tumoural function of sVEGFR1-i13 in SQLC tumour cells, which contributes to their progression and escape from anti-angiogenic therapies. These data might help to understand why some SQLC patients do not respond to anti-angiogenic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…It has been demonstrated that tumorigenesis will be withdrawn if the signal pathways of tumor angiogenesis are blockaded [4]. Thus, angiogenesis inhibition may be a viable treatment approach for the highly vascular tumor types, such as ovarian cancer, lung cancer and breast cancer [5][6][7]. However, targeting single factor may produce drug resistance and compensatory angiogenesis because the roles of other factors may be strengthened [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that tumorigenesis will be withdrawn if the signal pathways of tumor angiogenesis are blockaded [4]. Thus, angiogenesis inhibition may be a viable treatment approach for the highly vascular tumor types, such as ovarian cancer, lung cancer and breast cancer [5][6][7]. However, targeting single factor may produce drug resistance and compensatory angiogenesis because the roles of other factors may be strengthened [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the expression of sVEGFR-1 by epithelial cells contributes to the corneal avascularity and its transfection in lacrimal glands has been shown to prevent the pathological corneal neovascularization [27,28]; the pathogenesis of pre-eclampsia, typically occurring in the last trimester of pregnancy, has been related to sVEGFR-1 production by placenta and subsequent neutralization of VEGF-A and PlGF signaling [29,30]; a low sVEGFR-1 to VEGF-A ratio has been correlated with higher tumor malignancy/invasiveness and poor patients' survival [31][32][33][34][35][36][37]. The sVEGFR-1 may also play a proangiogenic and protumoral action by activation of β1 integrin, which results in stimulation of endothelial cell adhesion and chemotaxis [38][39][40]. VEGF family members and their receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in addition to the transmembrane VEGFR1, soluble isoforms of the receptor (sVEGFR1s) which arise from cleavage of full-lenght VEGFR1 or from alternative splicing of VEGFR1 pre-mRNA are produced by endothelial and also tumor cells. sVEGFR1s have been implicated in many pathological functions such as tumor progression 3,4 . In addition, several clinical trials have shown that anti-angiogenic therapies up-regulate circulating levels of sVEGFR1s 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Together, these data support the notion that sVEGFR1-i13 exerts both pro- and anti-angiogenic functions on endothelial cells. Interestingly, we recently demonstated that sVEGFR1-i13 contributes to the progression and the response of Squamous Lung Carcinoma (SQLC) cells to anti-angiogenic therapies through the regulation of a β1 integrin/VEGFR autocrine loop 4 . Therefore, these data indicated that sVEGFR1-i13 also targets the tumor cells themselves.
Figure 1VEGF 165 regulates sVEGFR1-i13 expression in SQLC cell lines.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation